AN ANALYSIS OF STUDENTS’ ABILITY IN IDENTIFYING GENERIC STRUCTURE OF NARRATIVE TEXT AT SECOND GRADE OF SMA EKASAKTI PADANG - Elda Martha Suri; Yessy Marzona; Risa Pertiwi Ningsih (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ekasakti, 2023)
This research is motivated by the difficulties of students ability in identifying generic structure of narrative. The purpose of this research was to find out to describe the students ability in understanding generic structure of narrative text and to describe the students ability in determining main idea in paragraph of narrative text. Many student were not to able to identifying generic structure of narrative text and difficulty in finding main idea in paragraph of narrative text. This research was conducted at SMA Ekasakti Padang, in academic year 2021/2022. The researcher conducted this research based on the researcher experienced of teaching practice. This researcher used descriptive research. The population of this research is all of students at second grade of social science of SMA Ekasakti Padang, namely 10 students. In taking the sample, the researcher used total sampling technique and all of population are sample. The instrument of this research was a reading test. Kind of the test is multiple choice test, with a total were questions 25 questions. In collecting data, the researcher gives a test to students with a time of 60 minutes. In analyzing data, researcher used some steps in scoring rubric by Arikunto (2007). The data analysis results showed that the students ability in identifying generic structure of narrative text were good. With the following description, (1) The ability of students in identifying generic structure of narrative text were good (the students' average score were 72.4). Specifically, there were 5 students in the very good category, 2 students in the good category, 1 student in the fair category, 2 students in the weak category, and 0 students in the poor category. (2) The ability of students determining main idea of narrative text were good (the students' average score were 70). Specifically, there were 6 students in the very good category, 0 students in the good category, 1 student in the fair category, 0 students in the weak category, and 3 students in the poor category. From the results, the researcher concluded that students in identifying generic structure were good.